Quality of Life and Disability in Stroke Survivors - Shakya, Dayana; Chaudhary, Rosy; Shakya, Dipesh; Shakya, Bikram (Journal of Karnali Academy of Health Sciences, 2019)
Background: With advancing treatment of stroke patients, their mortality has decreased but morbidity and disability has increased. Hence, it becomes increasingly important to find the measures to improve these areas. The study aims to assess the quality of life (QOL) and disability in stroke survivors at least six months post stroke. Methods: Descriptive, cross sectional design was used to assess the QOL and disability in stroke patients attending Neuromedicine and Neurosurgery out-patient departments of Kathmandu Medical College. Data was collected purposively using interview from 155 respondents. QOL was assessed using Health Related Quality of Life in Stroke Patients (HRQOLISP-40) and disability was measured by using World Health Organization Disability Assessment Schedule 2.0 (WHODAS 2.0). Analysis was done using Pearson’s correlation and Mann Whitney U test. Results: The QOL was found to be best in the ‘ecosocial’ and worst in the ‘soul’ domain. In disability, patients scored the best in ‘Getting along with people’ and ‘self-care’ domains and worst in the ‘life activities: school/ work’ domain. Respondents with hemorrhagic stroke, only one admission and those who did not exercise had better QOL. Patients with less than 10 years of formal education, those not earning and those with comorbidities had more disability. Correlation analysis showed better QOL with lesser age, higher monthly family income and higher Barthel index whereas higher disability was found in respondents with higher age and lower Barthel index. Conclusions: Disability in stroke patients needs to be addressed inorder to improve their QOL. The domains affected should be given attention during rehabilitation of stroke patients.